Improved fire severity mapping in the North American boreal forest using a hybrid composite method. Issue 2 (27th September 2021) - Holsinger, Lisa M.; Parks, Sean A.; Saperstein, Lisa B.; Loehman, Rachel A.; Whitman, Ellen; Barnes, Jennifer; Parisien, Marc‐André
Abstract: Fire severity is a key driver shaping the ecological structure and function of North American boreal ecosystems, a biome dominated by large, high‐intensity wildfires. Satellite‐derived burn severity maps have been an important tool in these remote landscapes for both fire and resource management. The conventional methodology to produce satellite‐inferred fire severity maps generally involves comparing imagery from 1 year before and 1 year after a fire, yet environmental conditions unique to the boreal have limited the accuracy of resulting products. We introduce an alternative method – the 'hybrid composite' – based on deriving mean severity over time on a per‐pixel basis within the cloud‐computing environment of Google Earth Engine. It constructs the post‐fire image from satellite data composited from all valid images (i.e., clear‐sky and snow‐free) acquired in the time period immediately after fire through the early growing season of the following year. We compare this approach to paired‐scene and composite approaches where the post‐fire time period is from the growing season 1 year after fire. Validation statistics based on field‐derived data for 52 fires across Alaska and Canada indicate that the hybrid composite method outperforms the other approaches. This approach presents an efficient and cost‐effective means to monitor and explore trends and patterns across broad spatial domains, and could be applied to fires in other regions, especially those with frequent cloud cover or rapid vegetation recovery. Abstract : We introduce a novel method to develop fire severity maps for North American boreal forests where mean severity is derived over time on a per‐pixel basis within the cloud‐computing environment of Google Earth Engine. This approach – called the 'hybrid composite' method – takes post‐fire imagery from two seasons – immediately after fire and spring and early summer of the following year – as opposed to conventional methods which use imagery from 1 year after fire. We compare satellite‐derived fire severity maps to field‐based measures for 52 fires in Alaska and Canada, and demonstrate the overall high performance of the hybrid composite method.